One Pot Silane Mediated Reductive Amination using Methyl Esters as Nominal Electrophiles - Cooke, Ishbel (2024)
Reductive aminations are a commonly employed method of C−N bond formation with a quarter of C−N bond formations in pharmaceutical synthesis performed via a reductive amination. Conventional reductive amination reactions rely on aldehydes as electrophiles which can be difficult to handle as a result of aldol dimerisation and autooxidation. This poster describes a new class of reductive amination reaction in which readily available carboxylic acid esters are used as nominal electrophiles in place of aldehydes. The amination process involves organocatalytic amide formation followed by silane-mediated reduction of the derived amide. The thesis describes the optimisation, scope, and mechanism of this novel amination protocol.